Combination of N-acetyl Cysteine and Thymoquinone Alleviates Hepatocellular Toxicities by Radiation and CCl4 Intoxication in SD Rats - Zhang, Shu; Chen, Shaohua; Wang, Jingyi; Sun, Qingyu; Alahmadi, Tahani Awad; Natarajan, Nandakumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Radiation and chemicals were the major clinical toxicants known to cause cellular damage during prognostic interventions in vivo. Cellular and molecular damages in the liver were the major causes for the hepatocellular injury due to various toxicities. Though many antioxidants alleviate various types of hepatotoxicities, protection exerted by the combination of N-acetyl cysteine (NA) and Thymoquinone (TQ) in the combined toxicities of radiation and carbon tetrachloride (CCLR) in Sprague-Dawley (SD) rats were unknown. Current research was focused on the protective efficacy of combination of NA with optimized dose of TQ (NATQ) in radiation/CCl4 (CCLR)-induced hepatotoxicities. At the end of the experimental period (6 weeks), body weight, liver weight, serum and liver tissues were analyzed for marker enzymes (AST, ALT, LDH), oxidative stress level (MDA, GSSG), antioxidant status (GSH, Vitamin E, Vitamin C), activities of enzymatic antioxidants (SOD, GPx, CAT, GST), liver histopathology and studies for the hepatic levels of NfkB, IL-6, TNF-α, MMP-3, MMP-12, Nrf2 and HO-1 were done. Significant (p≤0.05) toxicological alterations in the above parameters were recovered to normal in the treatment of NATQ combinations in SD rats. In conclusion, we provide evidence of protective efficacy of NATQ combination in alleviating the hepatotoxicities produced by CCLR in SD rats.
Keywords: N-acetyl cysteine; Thymoquinone; Carbon tetrachloride; Radiation toxicity; NfkB; MMP